2011
DOI: 10.1074/jbc.m110.212407
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Characterization, and Epitope Mapping of Neutralizing and Protective Monoclonal Antibodies against Staphylococcal Enterotoxin B-induced Lethal Shock

Abstract: T-cell stimulating activity of Staphylococcal enterotoxin B (SEB) is an important factor in the pathogenesis of certain staphylococcal diseases including SEB mediated shock. SEB is one of the most potent superantigens known and treatment of SEB induced shock remains a challenge. We generated and characterized murine monoclonal antibodies (mAbs) to SEB in mice. We tested mAbs neutralize mitogenic effects of SEB in vitro and in vivo with T-cell proliferation assays and 2 murine models for SEB induced lethal shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…Despite sensitivity to antibiotics, complicated S. aureus infections still have high mortality and treatment failure rates (37,38). Several studies demonstrate that neutralization of SAgs with drugs or Abs improves outcomes in both intoxication and infection models (39)(40)(41)(42)(43). Specifically, a recent study from our laboratory performed with MAbs specific to SEB provides encouraging data with respect to the development of such Abs as adjunctive therapy for complicated S. aureus infections (44).…”
Section: Discussionmentioning
confidence: 87%
“…Despite sensitivity to antibiotics, complicated S. aureus infections still have high mortality and treatment failure rates (37,38). Several studies demonstrate that neutralization of SAgs with drugs or Abs improves outcomes in both intoxication and infection models (39)(40)(41)(42)(43). Specifically, a recent study from our laboratory performed with MAbs specific to SEB provides encouraging data with respect to the development of such Abs as adjunctive therapy for complicated S. aureus infections (44).…”
Section: Discussionmentioning
confidence: 87%
“…While cooperativity and synergism of monoclonal antibody mixtures have been reported in the past (16)(17)(18)(19), emerging data have illustrated striking examples of situations wherein the activity of a monoclonal antibody can be drastically altered when assessed in the context of other antibodies (20,21). Indeed, the benefits of using polyclonal antibody preparations to treat disease in therapeutic settings are just beginning to be realized (22).…”
mentioning
confidence: 99%
“…Furthermore immunization with GST-mTSST-1 strongly induced the production of TSST-1 specific antibodies, especially immunoglobulin G1 and immunoglobulin G2b (Cui et al, 2005). Varshney et al, 2010 showed that four murine monoclonal antibodies bind to conformational epitopes that are destroyed by deletion of the distal C-terminal 11 Amino acids (Varshney et al, 2010). This study, for the first time, showed that MRSA derived SEB (staphylococcal enterotoxin B) contains a deletion in the C-terminal, which affects binding of certain protective Abs.…”
Section: Staphylococcal Enterotoxin As a Vaccine Candidatementioning
confidence: 91%
“…Picomolar concentrations of these superantigenic toxins activate specific T-cell subsets after binding to major histocompatibility complex class II. Activated T-cells vigorously proliferate and release proinflammatory cytokines plus chemokines that can elicit fever, hypotension, and other ailments which include a potentially lethal shock (Larkin et al, 2009, Varshney et al, 2010.…”
Section: Staphylococcal Enterotoxin As a Vaccine Candidatementioning
confidence: 99%